Investigating the Entrepreneurial Orientation, Perceived Environmental Hostility, and Strategy Application Among Saudi Arabian Small and Medium Size Businesses During the COVID-19 Pandemic - Alsoaery, Abdulrahman; Eshehri, Abdulrhman (Advances in Social Sciences Research Journal, 2023)
Little is known about how Saudi small and medium-sized enterprises are responding to the unfolding Covid-19 pandemic. This study assumes that when an economic crisis is unfolding, entrepreneurial Saudi SMEs perceive their environments as more hostile than their non-entrepreneurial counterparts. The perceived environmental hostility presented by the Covid-19 pandemic may drive the entrepreneurial firms to select diverse strategies to weather the crisis. A quantitative survey study, involving a number of SMEs drawn from Saudi Arabia, was used to confirm these hypotheses. Participants completed an online questionnaire to provide insights into the linkage between entrepreneurial orientation, the perceived environmental hostility presented by the coronavirus pandemic, and survival strategies employed by their firms during the pandemic. It is expected that the findings of this study will inform struggling SMEs in emerging economies about the best strategies to employ as they navigate the unfolding crisis caused by the ongoing Covid-19 pandemic.